POTENSI SERAPAN CO2 PADA BEBERAPA JENIS KANTONG SEMAR (Nepenthes spp.) DATARAN RENDAH [Potency of CO2 Absorption of Lowland Pitcher Plants (Nepenthes spp.)] - Mansur, Muhammad (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Pitcher plants (Nepenthes spp.) that known as âCarnivorous plantsâ, has a role in CO2 absorption. However, how much contribution to the CO2 absorption has not been studied. This study was aimed to provide information on CO2 absorption of some Nepenthes species particularly lowland species. This study was conducted at Research Center for Biology-Indonesian Institute of Sciences, Â Cibinong Science Center, Cibinong-West Java in June 2014 . A portable LCi ADC Bioscientific Ltd. Photosynthesis System was used to measure the absorption of CO2 directly. Measurement was conducted on 45 individuals of 15 species of Nepenthes with three replications for each species. The results showed that there was a variation of CO2 absorption rate on the lowland Nepenthes species, which was between 3.74 to 12.15 Âµmol m-2 s-1. The highest CO2 absorption was N. mirabilis (12.15 Âµmol m-2 s-1), followed by N. gracilis (9.71 Âµmol m-2s-1) and N. reinwardtiana (9.30 Âµmol m-2 s-1). While the lowest CO2 absorption occured in N. ampullaria (3.74 Âµmol m-2 s-1), N. hispida (3.75 Âµmol m -2 s-1) and N. bicalcarata (4.53 Âµmol m-2 s-1). Mature leaves of each species were recorded to have a highest CO2 absorption, transpiration and chlorophyll content than those of the young leaves. Â Â